Transpiration response to vapor pressure deficit and soil drying among quinoa genotypes (Chenopodium quinoa Willd.). Issue 2 (4th March 2021) - Sanchez, Maria; Sinclair, Thomas R.; Pradhan, Deepti
ABSTRACT: Water-deficit conditions limit increasing crop yield around the world. In order to improve crop yield it has been proposed to decrease water use early in the season so more water will be available later in the season to support seed growth during reproductive development. To achieve this, there are two water-conservation traits of special interest: partial stomatal closure under high vapor pressure deficit (VPD) and early in the soil drying cycle. Quinoa ( Chenopodium quinoa Willd.) is well known for its ability to grow in poor soils and extreme climatic environments. Therefore, quinoa may especially benefit from expression of water-conservation for water-limited conditions. These traits have not been previously studied in quinoa. This study reported the response of eight quinoa genotypes. Genotypes Red head, CICA-17, Salcedo, Ollague, Good Afternoon, and Pasankalla expressed a VPD breakpoint (BP) but Titicaca and French Vanilla not. All genotypes expressed a FTSW threshold with soil drying as expected. French Vanilla had the highest threshold, so it would be a candidate as a water-conserving genotype. The results of this study can be applied directly in field tests comparing cultivars under water-deficit conditions, and selection of genotypes to be used in breeding for improved cultivars specifically for drought.